Understanding Patient Anxiety and Perceived Sympathetic Responses during Endoscopic Ultrasound Procedures: A Qualitative Study - Qaiser, Ayesha; Sarmad, Sarmad; Sultan, Qandeel; Mahmood, Sidra; Ullah, Saadat; Khan, Tanweer (Journal of Neonatal Surgery, 2025)
Background: Endoscopic ultrasound (EUS) is one of the most vital tools of modern gastroenterology, serving both diagnostic and therapeutic purposes. Despite its value, patients often experience significant anxiety due to concerns about invasiveness, sedation, complications, and cost. Anxiety is not only psychological but also involves physiological responses mediated by the autonomic nervous system and stress hormones. Objective: To explore patients’ perceptions of anxiety and their perceived sympathetic body responses during endoscopic ultrasound. Methods: Semi-structured interviews were conducted with patients undergoing or scheduled for EUS preceded by ethical approval from research committee of MMC General Hospital Peshawar. The study duration was six months from January 2025 to June 2025. Thematic analysis identified patient concerns, experiences, and perceptions. Key themes included invasiveness, anesthesia, cost, complications, and physiological stress. Results: Patients reported high levels of fear, often related to sedation, possible complications, and financial burden. Anxiety manifested physiologically as tachycardia, flushing, sweating, and altered breathing. Pre-procedure counseling, adequate sedation (including benzodiazepines or dexmedetomidine), and educational interventions (videos, pamphlets) were effective in reducing anxiety. Social and cultural factors played a lesser role than financial and physiological concerns. Conclusion: Patient anxiety in EUS is both psychological and physiological, influencing comfort and procedural outcomes. Addressing this requires multidisciplinary collaboration, pre-procedural counseling, patient education, anxiolytic medications, and possibly non-pharmacological approaches such as mindfulness. Recognition of the physiological basis of anxiety,sympathetic activation, cortisol surge, and autonomic imbalance highlighting the need for holistic preparation strategies